Clinical presentation and treatment outcome of retinoblastoma in children of South Western China. Issue 42 (October 2016) - Gao, Jingge; Zeng, Jihong; Guo, Bo; He, Weimin; Chen, Jun; Lu, Fang; Chen, Danian
Abstract : Abstract: To study the clinical presentation and treatment outcome among children in South Western China with retinoblastoma (RB) and to determine factors predictive of poor outcome. A retrospective review of children diagnosed with RB from 2006 to 2015 at West China Hospital was undertaken. Demographic and clinical characteristics and treatment outcomes were studied. A total of 253 patients (unilateral 80.2%, bilateral 19.8%) were studied. Twenty six patients (10.3%) were from minority ethnic groups of China. The median onset age was 21 months. Leukocoria was the most common presenting sign (71%). Tumors were intraocular in 91.3% cases, extraocular in 8.7% cases. Extraocular RB patients had a longer median lag period than intraocular patients (9 months vs 2 months, P < 0.0001). In the intraocular group, 89.5% were advanced group D or E diseases. Enucleation was the major treatment for intraocular RB. However, over 10 years, the enucleation rate decreased constantly while more patients received chemotherapy. The Kaplan–Meier survival probability was 87.8%, 81.4%, and 74.8% at 3 years, 5 years, and 10 years, respectively. On Cox regression analysis, extraocular RB ( P = 0.0008) and treatment abandonment ( P < 0.0001) were associated with poor outcome; bilateral RB ( P = 0.0116) and advanced pathological grade pT4 ( P = 0.0011) were associated with poor outcome of intraocular RB. Most RB patients from South Western China were diagnosed at advanced clinical stage. Delayed presentation is related to extraocular RB which is a risk factor for poor outcome. Chemotherapy increased the eye salvage but had no effects to overall survival. Education for parents and general physicians for the early signs of RB (such as leukocoria), therapeutic strategy and treatment outcomes of RB may promote early diagnosis, improve the compliance, and outcome.